(untitled) (Journal of Global Accounting, 2022)
This study examines the effect of board characteristics on share price volatility of insurance companies listed on Nigerian Exchange Group. The study employed ex-post facto research design to establish the relationship between board size, board ownership, frequency of board meetings, and share price volatility. Secondary data were extracted from audited annual reports of twenty-four (24) quoted insurance firms, covering 2009 to 2019 financial years, and analyzed using SPSS, version 23. Ordinary Least Squares (OLS) regression was employed in estimating the unknown parameters in the study’s model. Empirical results show that board size and frequency of board meetings exert significant and positive influence on share price volatility, while board ownership shows an insignificant and negative impact on share price volatility of the study companies. However, board size, board ownership, and frequency of board meetings have joint significant impact on share price volatility of listed insurance companies in Nigeria. This implies that corporate board practices and activities of board members are instrumental in achieving stability in the movement (fluctuation) of share prices of quoted insurance companies in Nigeria. The study recommends that listed insurance companies in Nigeria should avoid over bloated board size, while members of the Board who are shareholders should have the expertise needed for meaningful contribution/participation during board meetings. Also, too many board meetings in a financial year should be avoided, especially when some of the issues being discussed are not evidently in the best interest of shareholders.